Unemployment, unemployment duration, and health: selection or causation? - Stauder, Johannes (The European journal of health economics, 2019)
This study aims at disentangling the causal effects of unemployment on physical and mental health from the selection of the unhealthy into unemployment. To identify causal effects, it explores hypotheses concerning how physical and mental health deterioration gain additional momentum with a longer duration of unemployment. In contrast, mere selection into unemployment implies time-constant effects of unemployment on physical and mental health. Fixed-effects models are applied to data from the German Socio-Economic Panel (GSOEP, 2002-2014, 74,572 observations). Pointing at causal effects of unemployment, the findings show that physical health does not deteriorate before, during or immediately after the period in which individuals lose their jobs, but that deterioration gains momentum later. The effect further depends on age at transition to unemployment. In contrast, a large part of the poorer mental health of the unemployed might be due to the selection of the unhealthy into unemployment; mental health declines even before job loss. Only for people who experience unemployment early in life, mental health deterioration gains some momentum in the time after the transition, indicating a (weak) causal effect of unemployment on mental health for younger individuals.